2008
DOI: 10.1089/cap.2006.0141
|View full text |Cite
|
Sign up to set email alerts
|

Rebound Effects with Long-Acting Amphetamine or Methylphenidate Stimulant Medication Preparations among Adolescent Male Drivers with Attention-Deficit/Hyperactivity Disorder

Abstract: This study investigated whether OROS methylphenidate (OROS MPH, Concerta) or extended-release mixed amphetamine salts (se-AMPH ER, Adderall XR) were associated with worsening of driving performance, or drug rebound, relative to placebo 16-17 hours post-ingestion. Nineteen male adolescent drivers aged 17-19 with attention-deficit/hyperactivity disorder (ADHD) were compared on a virtual reality driving simulator and an on-road drive after taking 72 mg of OROS MPH, 30 mg of se-AMPH ER, or placebo. Medication was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 26 publications
1
34
0
1
Order By: Relevance
“…These improvements are likely attributable in part to improvements in symptoms of ADHD, particularly inattentive symptoms. Although one previous study demonstrated that extended-release mixed amphetamine salts at a dose of 30 mg did not improve the driving performance of adolescents [31], and at 16 h postingestion, it was associated with medication rebound [27], a more recent study demonstrated that this medication improved daytime simulator driving performance of adults at a dose of 50 mg [26].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These improvements are likely attributable in part to improvements in symptoms of ADHD, particularly inattentive symptoms. Although one previous study demonstrated that extended-release mixed amphetamine salts at a dose of 30 mg did not improve the driving performance of adolescents [31], and at 16 h postingestion, it was associated with medication rebound [27], a more recent study demonstrated that this medication improved daytime simulator driving performance of adults at a dose of 50 mg [26].…”
Section: Discussionmentioning
confidence: 92%
“…They found that amphetamine, but not atomoxetine, significantly improved performance on the driving simulator, as determined by the overall Driving Safety Score (composed of seven simulatorderived variables and self-reported response of number of crash-likely events) and reduced ADHD symptoms. However, Cox et al [27] reported that during on-road testing, long-acting mixed amphetamine salts were associated with more inattentive driving errors (eg, taking eyes off the road, running stop signs, crossing median line) 16 h after dosing compared with placebo, suggesting possible drug rebound effects, whereas the long-acting methylphenidate formulation (Concerta, Ortho-McNeil-Janssen, Titusville, NJ) was not associated with any decay in driving performance 16 h after dosing.…”
Section: Benefits Of Pharmacologic Interventionsmentioning
confidence: 99%
“…Positieve effecten op het rijgedrag van personen met ADHD zijn ook gerapporteerd voor stimulantia anders dan methylfenidaat, zoals langwerkende gemengde amfetaminezouten en lisdexamfetamine dimesylaat. Echter, ondanks de positieve effecten van langwerkende gemengde amfetaminezouten bestaat er ook enig bewijs dat 16-17 uur na inname het aantal fouten op de weg door onoplettendheid toeneemt, wat op mogelijke reboundeffecten zou kunnen wijzen [81]. Daarnaast is aangetoond dat ook niet-stimulantia (atomoxetine), die eveneens worden gebruikt voor de behandeling van ADHD, de rijvaardigheid van personen met ADHD kunnen verbeteren.…”
Section: Conclusieunclassified
“…Yet, there has been minimal research documenting such phenomena [139,140]. There is a case report of withdrawal hyperactivity and psychosis after suddenly stopping MPH due to concerns about depression and suicidal behavior in an 8-year-old boy after 3 years of treatment.…”
Section: Withdrawal and Reboundmentioning
confidence: 99%